The constitutional legitimacy of law officers in the United Kingdom - McCormick, Conor (London [England] : Hart Publishing, 2022)
"This book provides a detailed account of each law officer's functions and draws on that account as the basis for a broader conceptual analysis of their constitutional legitimacy. The constitutional legitimacy of law officers has been questioned repeatedly in recent years, on account of recurring controversies surrounding the discharge of their varied functions. Indeed, it has become increasingly clear that those functions enable law officers to play a highly influential part in the regulation and exercise of public power throughout the United Kingdom. This book argues that the most persuasive framework for analysing the offices which make up this diverse regime involves concentrating on the constitutional values of independence, accountability and trust which underpin it. Both aspects of the book - namely the explanation of individual functions and the conceptual analysis of collective legitimacy - are written in a holistic way which encompasses critical analyses about the Attorney General and Solicitor General for England and Wales; the Counsel General for Wales; the Lord Advocate, Solicitor General and Advocate General for Scotland, as well as the Attorney General and Advocate General for Northern Ireland."--
Part I -- 1. Introduction -- 2. Conceptualising Law Officers in the UK Constitution -- Part II -- 3. The Attorney General and Solicitor General for England and Wales -- 4. The Counsel General for Wales -- 5. The Lord Advocate, Solicitor General and Advocate General for Scotland -- 6. The Attorney General and Advocate General for Northern Ireland -- Part III -- 7. Constitutional Controversy and Law Officer Legitimacy -- 8. Conclusions
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Government attorneys -- Great Britain; Law enforcement -- Officials and employees -- Great Britain; Constitutional law -- Great Britain; Electronic books